Reading the market? Expectation coordination and theory of mind in asset pricing experiments - Bao, Te (2022)
Does the ability to ‘read the market’ homogenize expectations and, thus, reduce deviations from rational expectations equilibrium in learning to forecast experiments? To answer this question, we conducted a pre-registered quasi-experiment by composing the market groups based on the subject’s Theory of Mind (ToM) capabilities, elicited via the eye gaze test. On the aggregate level, we find the market with the highest ToM capabilities to form a price bubble that is about 40% smaller and coordinates better at about 75% on the price forecasts, compared to the group with the lowest ToM capabilities. However, we fail to find a significant effect between those groups comparing price and expectation dynamics.